Diagnostic accuracy of dipsticks test among clinically suspected urinary tract infected patients at National Hospital, Tanzania - Leonard Katunzi1; George Msema Bwire1; James Kalabashanga2; Lilian Nkinda3; Akili Mawazo4; Kennedy Daniel Mwambete1 (Open Journal of Bacteriology - Peertechz Publications, 2019)
Background: Dipstick test is a rapid test for diagnosis of urinary track infections (UTIs). Rapid test should be accurate so that does not give a lot of false results that may subject patients to wrong treatments especially when used alone. Therefore, this study was set to determine the diagnostic performance of dipsticks tests by comparing with a standard urine culture Methods: Microbiological investigations of urine samples suspected of UTIs were performed at Central Pathology laboratory, Muhimbili National Hospital, Dar es Salaam. Dipsticks tests (leucocyte esterase and nitrite) were immediately performed from the submitted urine samples. Both positive and negative samples by dipsticks were subjected to quantitative urine culture using cysteine lactose electrolyte defi cient agar (CLED). Diagnostic performance such as sensitivity, specifi city and predictive values were determined by cross tabulation using GraphPad prisms whereas the distributions of the culture-isolated bacteria were expressed in frequency and percentage. Type 1 error for signifi cance was 0.05.